UFOs: Reframing the Debate edited by Robbie Graham - Thieme, Richard (Journal of Scientific Exploration, 2018)
UFO studies are stuck in a rut. Mark Rodeghier, the Director of CUFOs (The Center for UFO Studies) states that “the field has been stagnating and has run afoul on the rocks of abductions, government coverups/disclosure, and the lack of quality sightings.” UFOs: Reframing the Debate is an anthology of fourteen essays edited by Robbie Graham, and an attempt to respond to that morass by creating a radical new perspective on UFOs. The very first essay, by Canadian science writer Chris Rutkowski, states the dilemma precisely: “UFO belief becomes cultlike when adherents become closed to any interpretation of UFOs as conventional phenomena, and become something closer to religious zealots.” Unfortunately, that insight characterizes most of rest of the essays in this book. Religious zealots there are, in abundance. UFOs: Reframing the Debate shoots at a high target – the wholesale revisioning of how to approach UFO studies. The contributors intend to alter fundamentally the way we approach the subject. To that end, Graham collects diverse perspectives ranging from a Marxist critique to likening UFO encounters to poltergeist activity. Some of the speculation in these essays is provocative and suggestive. I paused now and again to consider some interesting insights. So the collection does sometimes wing the target – the target being, how to best approach UFO phenomena as a significant field of inquiry, while not locking in to an interpretation of UFO phenomena as physical craft – the “nuts-and-bolts interpretation"? But there are no real bulls-eyes. Lapses in logic, imprecise language, and arguments directed mostly at an ETH (extra-terrestrial hypothesis) or nuts-and-bolts bogeyman undermine the intentions of these highly speculative ruminations. Rejection of materialism results in a never-never land of pure thought. I wanted to reach for a balloon full of dried peas to bang them on the heads as Jonathan Swift suggested we do to bring people back to earth. That lack of grounding undermines the seriousness of this undertaking.